Nível de atividade física e evolução intra-hospitalar de pacientes com síndrome coronariana aguda - Jorge, Juliana de Góes (2011)
Acute Coronary Syndrome (ACS), whose main pathological substrate is atherosclerosis, constitutes a major cause of morbidity and mortality in the modern world. Physical inactivity, present in 85% of the population, is considered a risk factor for the development of atherosclerosis. This investigation was conducted to determine the degree of physical activity in patients with ACS, using the International Physical Activity Questionnaire (IPAQ), consorting with the in-hospital prognosis. It is an observational and analytical study, using 215 subjects, consecutively, admitted with a diagnosis of ACS in cardiology reference hospital from July 2009 to February 2011. All volunteers answered a short version of IPAQ and were followed regarding the appearance of cardiovascular events (CVE) during hospitalization from standardized assessment administered by the investigator, corroborated with data from medical records. To evaluate the association between physical activity and presence of in-hospital complication, we chose the logistic regression technique to determine the odds ratio adjusted and unadjusted. The patients were admitted with a diagnosis of unstable angina (34.4%), Acute Myocardial Infarction (AMI) without ST elevation (41.4%) and AMI with ST elevation (24.2%), and were classified as sedentary (39.5%), insufficiently active (16.7%), assets (35.8%) and very active (7.9%). From the standpoint of baseline, the sedentary group was older (p = 0.001), showed higher frequency of prior episodes of congestive heart failure (0.01) compared to the others and has higher systolic blood pressure, (p = 0, 05) that group is very active. It was verified the presence of ECV in 49.8% of the sample, with a linear trend in increasing frequency of acute pulmonary edema (p = 0.01), recurrent ischemia (p = 0.03) and atrial fibrillation (p ˂ 0.001), as a decrement in the level of physical activity. The occurrence of in-hospital complication was associated with length of hospitalization (OR = 1.14) and sedentary lifestyle (OR = 5.78), regardless of age, systolic blood pressure and history of congestive heart failure. Therefore, it is concluded that physical inactivity predicts ECV during hospitalization of patients with ACS.